Computational Thinking in Mathematics Learning: Systematic Literature Review - Mitrayana, M.; Nurlaelah, Elah (Indonesian Journal of Teaching in Science, 2023)
Computational Thinking (CT) has contributed to changing curricula around the world and is needed by everyone. This study aims to determine the research focus related to Computational thinking in mathematics learning and its novelty. The method used in this study is the method with systematic literature review (SLR). The data taken comes from the Google Scholar and Scopus databases. The moderator variables involved in this study were the year of publication, level of education, research class, research methods, and research instruments. All of the data obtained is presented in a quantitative descriptive manner. The results of the research show that 2022 is the highest peak for publication. This research was dominantly conducted at the junior high school level. And the class that is widely used in research is class XI. The study is dominated by descriptive research methods with a qualitative approach. Instruments that are widely used are tests and interviews.